2014
DOI: 10.1021/ie5018817
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Switchable Aggregation Phenomena of Xanthene Dyes Adsorbed on Tungsten(VI) Oxide Colloid Surface

Abstract: The surface interactions between xanthene (XN) dyes, including rhodamine B, rhodamine 3B, rhodamine 19, rhodamine 6G, rhodamine 110, and rhodamine 123, and tungsten(VI) oxide (WO 3 ) colloid particles were investigated. These XN dyes were strongly adsorbed as monolayer onto the WO 3 surface via the electrostatic interaction between their peripheral cationic amino-substituents and negatively surfacecharged WO 3 colloid particles, and most of ones adsorbed eventually formed the stable π-stacked dimers.The geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 57 publications
1
31
0
1
Order By: Relevance
“…This suggested that the pH did not significantly affect head-to-head coupling between transition dipoles of dimers; however, it did significantly strengthen the head-to-tail coupling between transition dipoles. These changes also implied that the angle between two transition dipoles became larger and the couplings were weaken with pH increase [13] . Therefore, energy transfer between TAMRA dimers became less efficient and emission of TARMA dramatically increased [12a, 12b, 13] .…”
Section: Author Manuscriptmentioning
confidence: 96%
See 3 more Smart Citations
“…This suggested that the pH did not significantly affect head-to-head coupling between transition dipoles of dimers; however, it did significantly strengthen the head-to-tail coupling between transition dipoles. These changes also implied that the angle between two transition dipoles became larger and the couplings were weaken with pH increase [13] . Therefore, energy transfer between TAMRA dimers became less efficient and emission of TARMA dramatically increased [12a, 12b, 13] .…”
Section: Author Manuscriptmentioning
confidence: 96%
“…An additional small shoulder peak at 522 nm was due to association between monomeric TAMRA molecules in aqueous solution [11] . After the conjugation to GS-AuNPs, the strong absorption at 550 nm was split into two peaks: one peak was located at 522 nm and the other was red shifted to 557 nm, consistent with previous reports [12] on dimerization of TAMRA molecules, further confirming dipole-dipole couplings of TAMRA dimers on GS-AuNPs.Since both blue and red shifts in absorption of TAMRA were observed, according to wellknown molecular excitation coupling theory [12a] , the dimers of TAMRA are not parallel to each other but have intermediate geometries [13] .While both monomeric TAMRA and GS-AuNPs are insensitive to pH changes from 6 to 10 (Figure 2A), TAMRA exhibited strong pH-dependent emission after being conjugated onto GS-AuNPs. As shown in figure 2B, with the increase of the pH value from 6 to 10, the fluorescence intensity at 587 nm gradually increased for more than 5 times while the emission intensity from the GS-AuNPs changed less than 10% in this range.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…同时, 在 pH 敏感型荧光材料 [4] 、激 光技术 [5] 和染料 [6] 等方面也有很好的应用. 随着氧杂蒽 在各领域上的广泛应用, 其在合成方面备受人们关注, 且在近几年出现了很多合成氧杂蒽的方法 [7~9] .…”
unclassified